2020
DOI: 10.1007/s10554-020-01883-9
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular global longitudinal strain in bicupsid aortic valve patients: head-to-head comparison between computed tomography, 4D flow cardiovascular magnetic resonance and speckle-tracking echocardiography

Abstract: Left ventricular global longitudinal strain (LVGLS) analysis is a sensitive measurement of myocardial deformation most often done using speckle-tracking transthoracic echocardiography (TTE). We propose a novel approach to measure LVGLS using feature-tracking software on the magnitude dataset of 4D flow cardiovascular magnetic resonance (CMR) and compare it to dynamic computed tomography (CT) and speckle tracking TTE derived measurements. In this prospective cohort study 59 consecutive adult patients with a bic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…This finding is consistent with the findings of Ciro Santoro, Maurizio Galderisi, et al ( 2019) on subjects with MR and S. Yilmazer; R.G. Chelu, et al ( 2020), who discovered that EDV and ESV were well correlated with GLS (r > 0.61, p 0.01) 20,29 .…”
Section: Characteristics Of Gls Index and Correlation Between Gls Ind...supporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with the findings of Ciro Santoro, Maurizio Galderisi, et al ( 2019) on subjects with MR and S. Yilmazer; R.G. Chelu, et al ( 2020), who discovered that EDV and ESV were well correlated with GLS (r > 0.61, p 0.01) 20,29 .…”
Section: Characteristics Of Gls Index and Correlation Between Gls Ind...supporting
confidence: 91%
“…Research S. Yilmaze, R.G. Chelu, et al (2020) discovered that EF correlates well with GLS 29 . Lima MSM, Villarraga HR, et al (2017) also showed that the GLS of STE was strongly positively correlated with LVEF, particularly in LV systolic failure 30 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the popularity of the CT-derived strain method is growing, and the methodology itself is standardized, as shown by recently published studies [ 33 ]. Studies from recent years indicate high repeatability of strain assessment in computed tomography, also high compliance with echocardiographic assessment or magnetic resonance imaging assessment [ 12 , 34 ]. In our study the reliability of the CT-derived strain evaluation was achieved by performing all tests on the same CT machine according to exactly the same image acquisition protocol, using a high-quality dedicated application for strain evaluation of a recognized company, evaluating the strain strictly according to the application instructions by an experienced researcher with practical skills certified by internationally recognized scientific societies, the use of manual correction of the initial automatic contour of endocardium and epicardium as well as an internal assessment of the repeatability of the assessment by determining the intra-observer and inter-observer variability.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that there was a high correlation between CMRFT and 2D/3D STE for LV strain. [16][17][18] Data that reflected LV diastolic function included LAVI and E/e' (E/Em). LVMI reflected LV hypertrophy.…”
Section: Discussionmentioning
confidence: 99%